Exploring the Impact of Virtual and Augmented Reality in International Brand Communication : A Case Study of Meta Company - Baldina, Diana; Bahles, Michael; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the integration of Augmented Reality (AR) and Virtual Reality (VR) technologies into international brand communication strategies. Using Meta as a case study, the research adopts a mixed-methods approach, combining a comprehensive literature review, content analysis of Meta’s AR/VR brand campaigns, and a quantitative online survey. The study tests three hypotheses: 1) AR and VR enhance consumer engagement more effectively than traditional digital branding methods; 2) brands that implement immersive technologies are perceived as more innovative and forward-thinking; and 3) the likelihood of adoption increases when users perceive AR and VR as both useful and easy to use. The findings confirm that AR is more commonly utilized than VR due to higher accessibility. Yet, both technologies show a positive trend in improving consumer engagement, strengthening perceptions of brand innovativeness, and—consistent with the Technology Acceptance Model—supporting adoption when perceived as beneficial. The thesis brings original insight by linking consumer perceptions with the strategic use of immersive tools in branding, offering a broader understanding of their role in global brand communication.
Vedoucí práce: Michael Bahles
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses